Governance, business and the environment - Sulaiman, Maliah (2013)
Traditionally, discussions on corporate governance (CG) have largely focused on economic sustainability. This is not surprising as CG issues have largely arisen out of accounting irregularities uncovered at prominent organizations, such as Enron, Tyco and WorldCom, and various other well-known companies. The focus of CG now, however, is broader….besides profits, companies are also focusing on the “people” and the “planet” too. Thus, the emphasis of CG today is on both the economic and environmental sustainability. Given this, boards cannot be lackadaisical about social and environmental issues. How can companies achieve this? According to the Coalition for Environmentally Responsible Economies (CERES) in its CERES Roadmap for Sustainability”, a sustainable company is one that has the necessary governance structures in place, extensive stakeholder engagement undertaken and the standards and scope of public disclosure and transparency instituted. Essentially, the Roadmap contains 20 specific expectations for corporate performance that are categorised into 4 main perspectives: governance, stakeholder engagement, disclosure and performance. Thus, companies should embed sustainability issues in management and board structures, goal-setting and strategic decision-making and engage in robust dialogue with stakeholders across the whole value chain. Additionally, companies should regularly report on sustainability strategies and performance. Disclosure will include credible, standardized, independently verified metrics encompassing all material stakeholder concerns, and detailed goals and plans for future action. Further, a sustainable company is one that embarks on achieving reductions in carbon emission and water use, procurement of renewable energy, improved energy efficiency and having a supply chain that meets high environmental and social standards. More importantly, companies are increasingly aware that a large part of their output consists of material waste (or non-product output). In particular, material flow cost accounting (MFCA), an environmental management accounting (EMA) tool that has now become an international standard, ISO 14051, can help companies address environmental issues as well as improve their bottom lines. Finally, to be proactive on environmental issues companies must understand and manage its environmental costs; introduce waste minimization schemes; understand and manage lifecycle costs; measure its environmental performance and embark on a strategic approach to environment related management. Most importantly, the tone should be set at the top. Top management commitment is essential, preferably at the board level. Accordingly, companies should ensure that directors’ skill sets include risk management of social and environmental issues. Most importantly, companies should realize that enhanced environmental performance can and will lead to improvement in the economic performance of the enterprise.